Examining Chlamydia trachomatis and Neisseria gonorrhoeae rates between 2010 and 2015: a population-based observational study. (July 2017) - Somayaji, R; Naugler, C; Guo, M; Church, D
Bacterial sexually transmitted infections including Chlamydia trachomatis and Neisseria gonorrhoeae remain an important public health concern. We aimed to assess the population-based incidence of C. trachomatis and N. gonorrhoeae in an age-standardized cohort over time. A retrospective study of a large Canadian health region was undertaken between 2010 and 2015 using linked census and digital laboratory data. C. trachomatis and N. gonorrhoeae tests were linked to patient data. Sex and age-standardized incidence rates (IR) and ratios (IRR) were calculated for cases and testing rates. The annual mean population was 1, 150, 556 individuals (50.1% female). A total of 15, 109 cases of chlamydia and 981 cases of gonorrhoea occurred. The overall IR for chlamydia ranged from 18.81 to 25.63 cases per 10, 000 person-years. The IRR was 1.27 (95% CI 1.20–1.34, p < 0.001) for the comparison of 2015 and 2010 rates. For gonorrhoea, overall rates ranged from 0.92 to 1.86 cases per 10, 000 person-years. The IRR for gonorrhoea was 2.02 (95% CI 1.56–2.59, p < 0.001) for 2015 and 2010 rates. In our large population-based study spanning six years, we observed increasing rates of C. trachomatis and N. gonorrhoeae with low testing rates.